Stompin' at the Savoy - Campbell, Bebe Moore, 1950-2006 (Philomel Books, 2006)
On the night of her jazz dance recital Mindy feels too nervous to go, until a magical drum whisks her away to the Savoy Ballroom in Harlem where she finds her "happy feet."